ON THE ISSUE OF THE RA BORDERING BELT SETTLEDNESS (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
More or less evenly settling of an area and effective use of resources it contains is a nationwide problem in the RA with special conditions of mountainous surface. In this sense, the analysis of settledness image, revelation of regional differences and current problems of bordering belt occupying almost a quarter of the RA territory are extremely actual and have a scientific and practical importance. The analysis and assessment of settledness level of an area, population and settlements distribution in the RA bordering belt are given in the article.
Keywords: population and settlement distribution; population density; occupancy